Los delitos sexuales cometidos por adolescentes infractores y sus consecuencias jurídicas - Calderon Cruz, Nathaly Nayeli (2025)
In Ecuadorian legislation, juvenile offenders follow a different and specialized legal procedure, focused on restorative justice and social rehabilitation. In cases of sexual offenses, the penalties established for adults are more severe than those for juvenile offenders, considering that the sentence duration is shorter and socio-educational measures are applied. For this study, a qualitative, non-experimental, cross-sectional research approach was used, with a descriptive scope. At the theoretical level, inductive, deductive, analytical, and synthetic methods were applied, while at the empirical level, documentary analysis and expert consultation methods were used. Additionally, interviews were conducted to gather expert opinions on the research problem. As a result, this study identifies the legal consequences of sexual offenses committed by juvenile offenders and discusses the statute of limitations for such crimes when the victims are children and adolescents.